Cytotoxic Effect of Benzofuranoid Neolignans from Myristica fragrans Seeds Against Melanoma B16-F10 Cancer Cells - Raihan Fathurrahman Hasbilla; Wahyu Safriansyah; Susianti Susianti; Desi Harneti; Suprianto Salam; Ronny Lesmana; Unang Supratman (Journal of Mathematical and Fundamental Sciences)
Myristica fragrans is an indigenous plant in Indonesia, characterized by various secondary metabolites with diverse bioactivities. This plant possesses promising anti-melanoma properties capable of addressing prevalent cases of melanoma. Therefore, this study’s objective was to isolate potential compounds from Myristica fragrans seeds and assess their cytotoxic effects on melanoma B16-F10 cells. Ethyl acetate extracts were subjected to separation through various chromatographic methods to obtain three benzofuranoid neolignans, which was conducted using spectroscopic analyses, namely UV-vis, polarimeter, HRTOF-MS, IR, and NMR. Subsequently, comparison with previously reported spectral data confirmed the identities of neolignans as (+)-licarin A (1), (+)-licarin B (2), and (+)-maceneolignan B (3). Cytotoxicity against melanoma B16-F10 cells was assessed using the PrestoBlue method, revealing (+)-licarin A (1) to display the most potent activity with an IC50 value of 94.15 μM.